Growth performance of Penaeus monodon(Fabricius) and carps in freshwater ponds underpolyculture - Ramanathan, N; Padmavathy, P; Francis, T; Athithan, S (Indian Journal of Fisheries, 2014)
The present paper deals with the polyculture of tiger shrimp, Penaeus monodonand carps in freshwater ponds. P. monodon seeds (PL 20) were stocked at therate of 1500 and 5000 no. / 0.1 ha under extensive and semi-intensive systemsrespectively. The carp fingerlings (catla, rohu, mrigal, silver carp, common carpand grass carp) were stocked at the rate of 400 and 800 no. /0.1 ha under extensiveand semi- intensive culture ponds respectively. Under extensive culture, theshrimp production obtained was 162.00 kg / ha / 122 days and it was 484.00 kg/ha / 123 days from semi-intensive culture. The carp production was 2409.40 and4855.00 kg / ha / yr under extensive and semi-intensive systems respectively.